Primary photodynamic therapy for small amelanotic choroidal melanomas: consecutive case series of 69 patients with at least 24-month follow-up. Issue 6 (16th July 2020) - Quhill, Hibba; Gosling, Daniel; Sears, Katharine; Rundle, Paul
Abstract : Aims: To investigate the success and recurrence rates and visual outcomes in a large case series of amelanotic posterior choroidal melanomas treated by means of primary photodynamic therapy (PDT) with verteporfin. Methods: Retrospective case series from a single specialist ocular oncology centre. All patients had a clinical diagnosis of choroidal melanoma and were selected for PDT based on tumour characteristics. Included patients had at least 24 months of follow-up from initiation of treatment and all but one had not received treatment prior to PDT. Results: 69 patients were included. Mean tumour thickness was 1.9 mm (range 0.5–4.4), while the mean basal diameter was 6.9 mm (range 2.4–11.0). Included lesions were stage cT1a (n=66) or cT2a (n=3). The mean duration of follow-up from treatment initiation was 57 months (range 24–116 months). Seven lesions (10%) failed to respond to PDT. 10 patients (16%) experienced recurrence during follow-up. Overall success rate in this series was 75% (n=52). 83% of successfully treated patients (n=43) maintained or gained vision by final follow-up. Visual outcomes were significantly better in those patients who received PDT therapy alone in comparison to those who needed other treatments for their melanoma (Fisher's exact test, p=0.004). Unfortunately, one patient (1.4%) in the series developed systemic metastases and died. Conclusion: Selected amelanotic posterior uveal melanomas may be successfully treated with PDT with retention of good vision in the majority of cases, maintained with a mean of 57 months (minimum of 24 months) of follow-up.